Search for non-standard neutrino interactions with the first six detection units of KM3NeT/ORCA - Aiello, S; Albert, A; Alhebsi, A.R; Alshamsi, M; Garre, S. Alves; Ambrosone, A; Ameli, F; Andre, M; Aphecetche, L; Ardid, M; Ardid, S; Aublin, J; et al. (Journal of Cosmology and Astroparticle Physics, 2025)
International audience KM3NeT/ORCA is an underwater neutrino telescope under construction in the Mediterranean Sea. Its primary scientific goal is to measure the atmospheric neutrino oscillation parameters and to determine the neutrino mass ordering. ORCA can constrain the oscillation parameters $Δ m^{2}_{31}$ and $θ_{23}$ by reconstructing the arrival direction and energy of multi-GeV neutrinos crossing the Earth. Searches for deviations from the Standard Model of particle physics in the forward scattering of neutrinos inside Earth matter, produced by Non-Standard Interactions, can be conducted by investigating distortions of the standard oscillation pattern of neutrinos of all flavours. This work reports on the results of the search for non-standard neutrino interactions using the first six detection units of ORCA and 433 kton-years of exposure. No significant deviation from standard interactions was found in a sample of 5828 events reconstructed in the 1 GeV$-$1 TeV energy range. The flavour structure of the non-standard coupling was constrained at 90% confidence level to be $|ε_{μτ} | ≤ 5.4 × 10^{-3}$, $|ε_{eτ} | ≤ 7.4 × 10^{-2}$, $|ε_{eμ} | ≤ 5.6 × 10^{-2}$ and $-0.015 ≤ ε_{ττ} - ε_{μμ} ≤ 0.017$. The results are comparable to the current most stringent limits placed on the parameters by other experiments.